(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
An institutional newspaper is a communication tool whose main objective is to convey information to an institution’s internal audience, disseminating information about the company’s services, events, and initiatives. These newspapers can be printed or online, and some are distributed across multiple platforms. This work is the result of research conducted in the Postgraduate Program in Information Science at the Federal University of Alagoas. The research analyzed the newspaper not only as a communication vehicle but also as a memory tool.